Multi-scale Opening of Conjoined Structures with Shared Intensities: Methods and Applications - Basu, S.; Raghavan, M. L.; Hoffman, E. A.; Saha, P. K. (2011 International Conference on Intelligent Computation and Bio-Medical Instrumentation, 2011)
We describe a new theory and algorithm for separating two structures sharing a common intensity band and conjoined at different unknown locations and scales. The method is applied for segmenting vasculature in patients with intracranial aneurysms via CT angiography (CTA). Major challenges in segmenting vasculature are related to separation of vessels and aneurysms from bone in the shared intensity space, especially, at regions with mutual tight coupling. The segmentation for bone and vessels combines fuzzy distance transform (FDT), a morphologic function with a topologic fuzzy connectivity to iteratively open two objects starting at large scales and progressing toward smaller scales. The accuracy of the method has been examined both qualitatively and quantitatively on (1) mathematically generated phantoms, (2) CT images of a pig pulmonary vessel cast phantom, and (3) cerebral CT angiography images of human subjects.